Understanding the Psychosocial Impact of Oral Squamous Cell Carcinoma (OSCC) on Patients - Ying, Wu; Ling, Tan Mei (2023)
With Oral squamous cell carcinoma (OSCC) is a cancer affecting the cells lining the oral cavity, posing significant emotional and social challenges for patients. This research aimed to explore the psychosocial impact of OSCC on patients' emotional, social, and psychological well-being. The study findings revealed several key aspects of the psychosocial impact of OSCC.Emotional distress emerged as a prominent consequence of an OSCC diagnosis, leading patients to experience fear, anxiety, sadness, and anger. The uncertainty surrounding the disease, treatment outcomes, and future prospects further intensified emotional burden and negatively influenced the overall quality of life.The study also highlighted the significant impact on body image and self-esteem due to physical changes resulting from OSCC treatments, such as facial disfigurement and difficulty in speech, eating, or swallowing. These changes created a sense of loss of identity and self-worth, affecting patients' self-esteem.Patients with OSCC encountered social isolation as they felt reluctant to interact with others or engage in activities due to the visible effects of the disease or treatment side effects. The fear of judgment or rejection led to a withdrawal from social gatherings, adding to their emotional distress.Cancer also strained relationships with family members, friends, and partners, leading to emotional distress for both patients and caregivers, altering the dynamics of the patient's support system. The financial burden of cancer treatment further exacerbated stress levels, impacting the patient's overall psychosocial well-being.Coping mechanisms varied among patients, with some seeking support from social networks or support groups, while others opted for professional counseling or therapy to manage emotional challenges effectively. Fear of cancer recurrence was a recurring concern even after successful treatment, affecting patients' mental health and daily life.The psychosocial impact of OSCC also had implications for treatment adherence, with emotional distress, depression, or anxiety leading to missed appointments or inadequate adherence to treatment plans.